Practice-oriented research in service of designing interventions - C. Hermans; W. J. Schoeman (Acta Theologica)
The strength of the practice-oriented research strategy is to develop knowledge about the improvement of practices. Practice oriented research is research in which the research goal is coming from the professional practice and in which the knowledge created in the research contributes directly to this professional practice. The problem does not originate in theory, and the knowledge created in the research is not valued because it contributes to theory. It is not knowledge-for-its-own-sake, but the knowledge is valued because it contributes to the improvement of the practice which is considered (by ministers and lay people) to be a problem. Practice-orientated research is especially relevant to congregational studies because the congregational ministry is conducted within a specific context that is challenging it to be relevant. The major steps or questions in developing a research design of practice oriented research is: what is the problem you are going to study? Why is it interesting to get this new knowledge and for whom is it interesting? How are you going to reach your research objective? How much do you want to know? And what are the conceptual instruments which you are going to use in your research? In following these steps the specific research orientation of practice oriented research is introduced.